Thuja Occidentalis l. Expedites Functional Recovery after Sciatic Nerve Crush Injury in Mice - Sanam Naz, Tahir Farooq, Arruje Hameed, Haseeb Anwar, Rizwan Aslam, Shoaib Ahmad Malik, Rabia Akram, Faiqa Sajid, Zakia Saeed, Ghulam Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
This study was conducted to find the potential of Thuja occidentalis (crude powder) in promoting the rate of recovery following the sciatic nerve injury in a mouse model. Thuja occidentalis was administered orally at a dosage of 2g/kg body weight. The motor functional recovery was measured using muscle grip force, sciatic functional index (SFI), and muscle weight. While the hotplate test and formalin test were performed to measure the recovery of sensory functions. Other biochemical tests were performed to analyze oxidative stress. We noted an early recovery of motor functions in the treatment group as determined by SFI (P<0.001) and grip strength test (P=0.01). Additionally, the mass of Gastrocnemius (P=0.04) and the Tibialis anterior (P=0.008) muscle was also recovered in response to the treatment. Similarly, it significantly expedites the recovery of sensory function as checked by the hotplate test (P=0.005). Moreover, the reduced oxidant status (P=0.03) and elevated antioxidants capacity (P=0.005) were also found in the treatment group. Collectively, all of these findings highlight that the Thuja occidentalis possesses the potential to accelerate functional recovery. The enhanced antioxidant capacity and reduced oxidants status of the biological system appears the possible reason for this improved functional regain after the sciatic nerve crush.